Miopati Atrium, Fibrilasi Atrium, dan Stroke: Mengungkap Hubungan Tersembunyi - Yamin, Muhammad; Azizi, Mohamad Syahrir; Putri, Anneira Amanda (Jurnal Penyakit Dalam Indonesia, 2026)
Atrial fibrillation (AF) is the most common arrhythmia and has been long recognized as a cause for atrial thrombus formation leading to cardioembolic stroke. However, recent studies reveal that the relationship between atrial fibrillation and stroke is an association rather than a temporal relationship. Left atrial thrombus formation is associated with vascular risk factor, atrial remodeling, and thrombogenesis. Various atrial electrical and structural markers of atrial myopathy have been linked to ischaemic stroke, even in the absence of AF. In addition to the CHA2DS2-VASc score as a consideration for anticoagulant administration, accurate atrial myopathy markers are needed to allow early identification of patients at risk for cardioembolic stroke. This article describes the current concept of atrial myopathy, including its pathophysiology, diagnostic approach, and stroke prevention.